Exploring relationship satisfaction a social exchange perspective on the interdependence between theory, research and practice - Sabatelli, Ronald M. ([Place of publication not identified] National Council on Family Relations, 1988)
This article explores the applications of the social exchange perspective on relationship satisfaction to educational and therapeutic interventions with those involved in close personal relationships. The article focuses on the role that relationship expectations play in the evaluations that people make of their relationships. A specific illustration of the relevance of this exchange perspective on relationship satisfaction for educational intervention with premarital couples is presented. Specifically, the educational implications of data contrasting the relationship expectations of exclusively dating and married couples and the males and females within each of these groups are explored.
Includes bibliographical references.
Keywords: Interpersonal relations; Prenuptial agreements